Accessibility and the bus system : transforming the world - Tyler, Nick, 1954- (London : ICE Publishing, 2016)
'Accessibility and the Bus System' explores the role of the bus system in enabling cities to function sustainably and efficiently by providing the necessary resources to support growing populations. The book takes a comprehensive view of what buses can and cannot do, and how to maximise the bus system's positive contribution while minimising the negative impacts.--
Previous edition published as: Accessibility and the bus system : from concepts to practice : London : Thomas Telford, 2002.
Includes bibliographical references and index.
Keywords: Bus terminals -- Barrier-free design; Bus lines -- Barrier-free design; Buses -- Barrier-free design